Bioenergy : biomass to biofuels and waste to energy - Dahiya, Anju (Academic Press, 2020)
Bioenergy: Biomass to Biofuels and Waste to Energy, 2nd Edition presents a complete overview of the bioenergy value chain, from feedstock to end products. It examines current and emerging feedstocks and advanced processes and technologies enabling the development of all possible alternative energy sources. Divided into seven parts, bioenergy gives thorough consideration to topics such as feedstocks, biomass production and utilization, life-cycle analysis, energy return on invested, integrated sustainability assessments, conversions technologies, biofuels economics, business, and policy.